Direct synthesis of plugged SBA-15 type mesoporous silica using alcoholamines. - Min, Byung-Hoon; Jeong, Eun-Young; Thommes, Matthias; Park, Sang-Eon (Chemical Communications, 2011)
Plugged mesoporous SBA-15 having a 2-D hexagonal pore structure could be directly synthesized under acidic conditions using P123 as a supramol. template, sodium metasilicate and alcoholamines. The use of alcoholamines seemed to play roles as capturing agents for silica sources that could form internal porous plugs. [on SciFinder(R)]
Keywords: SBA15 mesoporous silica plugged synthesis alcoholamine